Transformasi Jazz Yogyakarta: Dari Hibriditas menjadi Komoditas - Sutopo, Oki Rahadianto (UI Scholars Hub, 2012)
This article tries to show the transformation of jazz music as a cultural product in Yogyakarta. This transformation is, according to Baumann, fluid, contradictory, and ambivalent. In the origin, this music became a symbol of resistance by the lower class, whereas in Indonesia jazz became the upper middle class consumption. However, in its development, some jazz musicians try to restore the original meaning by combining local elements and bring a hybrid genre of jazz, although this was not last long. The traditional elements can not survive to bring the spirit of resistance because this new genre of jazz eventually entered the music industry as a pop culture. Local elements in the end are commodified. The impact is then the reduction of the meaning of jazz and locality itself.